The convergence of financial and management accounting in Poland - Kabalski, Przemysław; Zarzycka, Ewelina (Konwergencja rachunkowości finansowej i zarządczej w Polsce, 2018)
The aim of this article is to present the results of a study on the convergence of financial accounting and management accounting in companies operating in Poland against the background of international solutions. The survey, carried out in 2017, was used to collect data. Based on the questionnaire returned by 40 companies, it was found that the level of convergence of financial accounting and management accounting in Polish enterprises is moderate. The number of worldwide studies on the convergence of accounting is very limited, and in Poland they are quite unique. For this reason, the study presented in this article is relevant both for science and the practice of accounting
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 2, s. 9-19
Keywords: convergence; management accounting; financial accounting; konwergencja; rachunkowość finansowa; rachunkowość zarządcza; pomiar